Building Legal Awareness of Citizens Through Civic Participation Competence in Civic Education - Damayanti, Siska; Khairunisa, Wafa; Fajriani S, Nur (Centre for Literary and Cultural Studies, 2024)
The development of citizens' legal awareness is a critical aspect in ensuring the sustainability and stability of a country. Therefore, efforts to build citizens' legal awareness are also fostered through education. Civic Education is viewed as a strategic platform to build citizens' legal awareness, as one of the competencies in civic education is oriented towards civic participation. This research aims to explore the role of Civic Education in building citizens' legal awareness through the strengthening of Civic Participation competence. Using a qualitative approach and literature study method, this research reveals that through Civic Education, legal awareness can be developed using Project Citizen, Role Playing, and Debate teaching methods.